Optimization study of sub/supercritical water liquefication of lignite: Fast liquefaction for high bio-oil yield. (13th August 2019) - Liu, Chong; Li, Junjun; Lin, Yechun
Abstract: Sub/supercritical water liquefication (SCWL) is a water-based thermochemical technology as well as an environmentally friendly treatment by converting wet feedstock into bioenergy. In the present study, a systematic investigation of SCWL of lignite was carried out covering a temperature range between 320 and 440 °C when residence time increased from 5 min to 40 min. The highest bio-oil oil yield of 34.3% with solid residue of 52.7% was obtained at 440 °C for 5 min. Phenol derivatives, carboxylic acids, long chain hydrocarbons, ketones, and naphthalene were the main bio-oil composition through FTIR and GC-MS analysis. Gas yields and their exact compositions were also determined and CO2 was the dominate gas product but the percentage of CH4 became significant at severe SCWL conditions. A conclusion was drawn that fast liquefaction (e.g. 5 min) at relative higher temperature (e.g. 400 °C) which avoid excessive gasification and repolymerization reactions was an optimization strategy for high yield bio-oil production from SCWL of lignite. Highlights: A systematic investigation of lignite SCWL was carried out for bio-oil production. The condition was given for highest bio-oil production. The reason of low bio-oil yield was given at excessive SCWL condition. The component of gas, bio-oil, and solid products was discussed.